POLITENESS MAXIM OF MAIN CHARACTER IN SECRET FORGIVEN - Sang Ayu Isnu Maharani (LITERA : Jurnal Bahasa Dan Sastra, 2017)
ABSTRACT Maxim of Politeness is an interesting subject to be discussed, since politeness has been taught since our childhood. We are obliques to be polite to anyone either in speaking or behave.Somehow we  manage to show politeness in our spoken expression though our intention mightbe not so polite. For example we must appreciate other’s opinion although we have objection towards the opinion.In this study, the analysis of politeness is based on maxim proposes byLeech. He proposed six types of politeness maxims. The discussion shows that the main character (Kristen and Kami) use all type of maxim in their conversation. The most commonlyuse are approbation maxim and agreement maxim. Key Word : politeness, maxim ABSTRAK Kesantunan dalam komunikasi sangat menarik untuk dikaji, sebab kita telah diajarkan sopan santun sejak kita kecil. Kita diwajibkan untuk senantiasa santun kepada siapa pun baik dalamtuturan maupun tindakan. Seiring dengan waktu, kita mampu menunjukkan kesantunan dalam bertutur walaupun tujuan kita untuk mengkritik. Sebagai contoh, kita diharapkan mampumenghargai pendapat orang lain walaupun kita keberatan dengan pendapat tersebut. Dalam penelitian ini, analisis tentang kesantunan didasarkan atas teori yang dicetuskan oleh Leech.Leech membedakan kesantunan menjadi enam kelompok. Analisis menunjukkan bahwa Kristen dan Kami menggunakan semua bentuk kesopanan yang ada dalam tuturan mereka. Bentukyang paling umum di pergunakan adalah approbation maxim dan agreement maxim. Kata Kunci : kesopanan, tuturan